Seropositivity of hepatitis B, hepatitis C, syphilis, and HIV in antenatal women in India - Mehta, Krunal Dineshbhai; Antala, Sejul; Mistry, Madhulika; Goswami, Yogesh (The Journal of Infection in Developing Countries, 2013)
Introduction: The epidemiology of viral hepatitis during pregnancy is of paramount importance for health planners and program managers. Data on viral hepatitis during pregnancy are not readily available. This study was conducted to assess the extent of seropositivity of hepatitis B, hepatitis C, HIV, and syphilis in pregnant women and to re-evaluate the need for routine antenatal care screening. Methodology: All samples were tested to detect HBsAg by enzyme linked immunosorbent assay (ELISA). Samples were tested to detect anti-HCV by ELISA. Samples were also tested for antibodies to Treponema Pallidum by qualitative rapid plasma reagine (RPR); finally, samples were tested for antibodies to HIV by three different methods as per Strategy III of the National AIDS Control Organization by using different systems of testing to establish a diagnosis of HIV. Results: Seropositivity of hepatitis B was 2.9%, hepatitis C was 0.19%, syphilis was 0.48%, and HIV was 0.38%. Out of the 1038 samples, no co-infection was found between hepatitis B, hepatitis C, syphilis, or HIV. Conclusion: The data from this study can help health professionals to treat antenatal patients more effectively. The data also reinforces the need for establishing effective prevention programs, which could lead to a reduction in the prevalence of HBV, HCV, syphilis, and HIV